Teacher Training on Application of Historical Method in Teaching and Professional Development - Deletić, Zdravko M.; Virijević, Vladan A. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Contemporary teaching of social sciences has a goal of transferring selected knowledge to students with as much of their active participation in the process of teaching as possible, primarily, through student activity while working with documents and sources of knowledge. It is necessary to provide students with minimal methodological training so that they would know how to critically assess original documents. A teacher trains students methodologically through work with selected examples, which requires basic knowledge of historical method and source criticism. It is assumed that students use acquired knowledge for later continuous professional development and self-education. With the aim of satisfying these needs, teachers of history and of other socio-humanistic sciences should be trained to apply the historical method and source criticism – written documents – to their teaching practice. The authors present main challenges of working with written sources. The paper rooted in the literature survey and the summary of experiences in teaching and researching history.
Keywords: a history teacher; source criticism; historical sources; historical method